Pharmacokinetics of hepatitis C virus NS5A inhibitor JNJ‐56914845 (GSK2336805) in subjects with hepatic impairment. (25th May 2015) - Adkison, Kimberly K.; Gan, Jianjun; Elko‐Simms, Lucinda; Gardner, Stephen; Dumont, Etienne; Jones, Lori S.; Saunders, Joanne; Marbury, Thomas; Smith, William; Berg, Jolene; Galloway, Christopher; Stump, Patrick J.
Abstract JNJ‐56914845 (GSK2336805) is a hepatitis C virus nonstructural protein 5A inhibitor under development for the treatment of chronic hepatitis C (CHC) infection. This open‐label, parallel‐group, 2‐part study evaluated the pharmacokinetics and safety of a single oral 60 mg dose of JNJ‐56914845 in 4 cohorts: healthy, mild, moderate, and severe hepatic impairment (n = 8/cohort). Severity of hepatic impairment was categorized using Child‐Pugh score, and the healthy subjects were matched for age, sex, body mass index, and smoking status to the moderate hepatic impairment cohort. JNJ‐56914845 plasma AUC0–∞ was 26%, 52%, and 45% lower in subjects with mild, moderate, and severe hepatic impairment, respectively, relative to healthy subjects with no difference in half‐life among the groups. The apparent oral clearance and volume of distribution were higher in subjects with hepatic impairment. The lower plasma concentrations were largely explained by decreased plasma protein binding in hepatically impaired subjects. One subject with severe hepatic impairment had 2 non‐drug‐related serious adverse events: an esophageal bleed requiring hospitalization, encephalopathy. Although hepatically impaired subjects have lower exposures than healthy matched controls, they had similar or slightly higher exposures than those observed in past studies of noncirrhotic, CHC patients, suggesting that no dose adjustments for hepatic impairment will be needed.